Early release of constricting amniotic band of the lower limb followed by reconstruction using multiple Z-plasty - Fatimah I. Alabdrabalnabi; Ayman S. Elsaid; Fatima M. Alsinan; Hasan A. Almushrif; Mohammed A. Nasr; Ehab Elashaal; Reem K. Aljehani (Elsevier, 2021)
Amniotic Band Syndrome (ABS) or Constriction Band Syndrome, is a rare entity of congenital malformations characterized by various clinical manifestations. We present a case of ABS affecting the left lower limb along with left-hand syndactyly without any associated internal organs' anomalies. He was treated by a two-stage release surgery using multiple Z-plasty. We compared our result with three previously published cases using different surgical interventions.